Adenomyosis, Multiple, and Intraligamentery (Sacro Uterine) Fibroids: A Rare Case - Anas, Muhammad; Prasetyo, Ari Pudji; Jamil, Ahmad Mochtar (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Uterine leiomyomata, often known as fibroids, are frequently accompanied by symptoms that are common to a variety of different pelvic disorders. When considering treatment choices, it is critical to correctly identify myomata and rule out other disorders, including malignancies. In this case report, the author emphasizes the difficulty in establishing a preoperative diagnosis and the actions taken during the operation.Case report: Female, 46 years old, has three children who live with two children. She was complaining of left abdominal pain and penetrating to the waist. There were no complaints of defecation or urination. A mass in the lower abdomen, solid springy, and half of the symphysis center tend to the right with limited mobility. The preoperative diagnosis is pedunculated uterine myoma. It was decided to do a Supravaginal Hysterectomy and Bisalphingo-oforectomy. The pelvic cavity still looks bulging, and exploration was carried out to find uterine myomas of the intrasacrouterina ligament. Then, it was decided to do a Myomectomy.Conclusion:Pedunculated uterine myoma intrasacrouterina ligament performed Supravaginal Hysterectomy and Myomectomy